Web-based sustainability reporting by family companies: The role of the richest European families - Palma, M.; Lourenço, I.; Branco, M. (Accounting Forum, 2022)
This study compares the sustainability reporting practices of family companies with those of their non-family counterparts and examines whether the former owned by billionaires engage differently with sustainability reporting compared to their counterparts. The empirical analysis is based on 360 companies from 17 European countries. A propensity score matching (PSM) procedure was adopted and we selected 180 family companies and 180 non-family companies. The former group includes 90 owned by European billionaires listed in the Forbes 2019 World Billionaires Ranking and 90 not owned by billionaires. Findings are consistent with the argument that family companies attach greater importance to sustainability reporting. Within the family company arena, findings reveal that greater prominence is attributed to sustainability issues on corporate websites when the family company’s CEO is a family member and the level of family ownership is lower. The results revealed mixed evidence regarding differences between family companies owned by billionaires and their counterparts. The prominence attributed to sustainability issues on corporate websites by family companies owned by European billionaires is greater than that of family companies not owned by billionaires, but only when using a less stringent measure of prominence. These findings emphasise the importance of exploring family companies as a heterogeneous group.